Mould Infections of Traumatic Wounds: A Brief Narrative Review - Giacobbe, Daniele Roberto (Infect Dis Ther, 2020)
Mould infections may follow traumatic injuries, with direct fungal inoculum in the site of injury and subsequent angioinvasion, possibly resulting in tissue necrosis and systemic dissemination. The pathogenesis of mould infections following trauma injuries presents unique features compared with classical mould infections occurring in neutropenic or diabetic patients, because a large fraction of post-traumatic mould infections is observed in previously healthy individuals. Most of the published clinical experience and research on mould infections following traumatic injuries regards soldiers and infections after natural disasters. However, following trauma and soil contamination (e.g., agricultural or automotive injuries) other immunocompetent individuals may develop mould infections. In these cases, delays in correct diagnosis and treatment may occur if pertinent signs such as necrosis and absent or reduced response to antibacterial therapy are not promptly recognized. Awareness of mould infections in at-risk populations is needed to rapidly start adequate laboratory workflow and early antifungal therapy in rapidly evolving cases to improve treatment success and reduce mortality.